Rotational Spectrum and Conformational Analysis of N-Methyl-2-Aminoethanol: Insights into the Shape of Adrenergic Neurotransmitters - Calabrese, Camilla; Maris, Assimo; Evangelisti, Luca; Piras, Anna; Parravicini, Valentina; Melandri, Sonia (Frontiers in Chemistry, 2018)
Abstract We describe an experimental and quantum chemical study for the accurate determination of the conformational space of small molecular systems governed by intramolecular non-covalent interactions. The model systems investigated belong to the biological relevant aminoalcohol’s family, and include 2-aminophenylethanol, 2-methylaminophenylethanol, noradrenaline, adrenaline 2-aminoethanol and N-methyl-2-aminoethanol. For the latter molecule, the rotational spectrum in the 6-18 and 59.6-74.4 GHz ranges was recorded in the isolated conditions of a free jet expansion. Based on the analysis of the rotational spectra, two different conformational species and 11 isotopologues were observed and their spectroscopic constants, including 14N-nuclear hyperfine coupling constants and methyl internal rotation barriers, were determined. From the experimental data a structural determination was obtained, which was also used to benchmark accurate quantum chemical calculations on the whole conformational space. Atom in molecules and non-covalent interactions theories allowed the characterization of the position of the intramolecular non-covalent interactions and the energies involved, highlighting the subtle balance responsible of the stabilization of all the molecular systems.